Towards a framework of pedagogical content knowledge in Entrepreneurship Education for Technical Vocational Education and Training College lecturers - Motsoeneng, Molefi; Qhosola, M.R. (Technium Social Sciences Journal, 2021)
This study presents an intervention to design a framework to empower entrepreneurship education, Technical Vocational Education and Training College lecturers. The study is couched in the Critical Emancipatory Research paradigm whose criteria for quality are determined on the basis of advancing the agenda for equity, social justice, freedom peace and hope. The literature on Pedagogical Content Knowledge in entrepreneurship education is used to understand the challenges confronting the lecturer. The participatory action research approach was employed to generate data from discussion, class visits and meetings to understand and design a framework for effective teaching of entrepreneurship. The participants consisted of entrepreneurship lecturers, a parent, students, head of department and a local businessman. The data was collected from a series of meetings, discussions and workshops. The findings reveal that Technical Vocational Education and Training College lecturers lack pedagogical content knowledge. Therefore, a framework for teaching entrepreneurship is presented.